Short-term outcomes of treatment of active stage of Charcot foot in outpatient setting - Anastasia G. Demina; Vadim B. Bregovskiy; Irina A. Karpova (Сахарный диабет)
Background: Treatment options in patients with an acute Charcot foot is not well standardized and still challenging.Aims: To evaluate the results of the non-operative treatment of patients with active stage of diabetic charcot arthropathy in outpatient foot clinic and to identify factors influenced on treatment results.Materials and methods: Medical files of 141 patients with unilateral ulcer-free active charcot arthropathy were reviewed. 78 patients agreed for treatment (total contact cast or walker), 63 patients refused of treatment (follow-up only). The time of resolution of the acute stage, severity of final deformities and foot-related complications were evaluated. Refusers were asked about the cause of their decision.Results: Mean delay of the diagnosis was 3,2±2,8 months. Main causes of the refuse were: mistrust to doctor - 38%, problems with employment - 33%, home/family problems - 18%, medical reasons - 11%. Median healing times (months) in the treatment group vs controls: 9 (6 - 19) 15 (13 - 25) (p=0,001) and progression of the initial deformity: 14% and 35%, respectively (p=0,01). Foot-related complications: 17,5% in the treatment group and in 55,6% of controls (including 6 amputations) (p=0,001). Frequency of breaking the cast/walker - 32%/16,6%. Foot lesions due to cast/walker: 13,6%/41,7% (p<0,01). Median healing times (months) with walkers - 13 (11 - 19), with casts - 9 (6 - 15) months (р=0,02). The use of crutches shortened healing time.Conclusions: The significant delay of diagnosis was revealed. The refuse rate in our cohort was high and main causes of the refuse were social and psychological. Neglect of treatment leads to high frequency and severity of foot-related complications. We noticed high rate of breaking of walkers and casts and device-related foot lesions. Total contact casts were more effective and safe compared with walkers.